PENOMENA TA’ARUF ONLINE; ANALISIS ISTISHAB DAN MASLAHAH MURSALAH - Ahmad Soleh Hasibuan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This paper discusses the phenomena that occur in cyberspace or what is known as the digitalization era, namely the ta'aruf process that uses online applications that need to be seen from a legal point of view, in this case using the method of ushul fiqh Istishab and Maslahah Mursalah. The method used in this paper uses the empirical method by looking at the developments of habits that occur in today's society, as well as by using data analysis contained in internet applications that develop in society. From an istishab perspective, the practice is legally permissible, although the practice of ta'aruf is carried out online from various social media such as Websites, Instagram, Facebook and others. That there is no argument that prohibits the practice of online ta'aruf and the online ta'aruf process does not conflict with Islamic law. The practice of ta'aruf online also has benefits that can be used by men or women who have difficulty getting a partner. However, in addition to the benefits, there are also obstacles and shortcomings that must be considered, including the rules for online ta'aruf participants and strict rules on the identity and profile of online ta'aruf participants